Assessment of craftsmen turnover in the construction industry / Calistus Ayegba and Adakole Edwin Agbo - Ayegba, Calistus; Agbo, Adakole Edwin (Faculty of Architecture, Planning & Surveying, 2015)
The paper gives an insight on construction craftsmen turnover in the construction industry. In the study, the main factors responsible for craftsmen turnover, the effect of craftsmen turnover on contractors’ performance and suggestions that will tackle the problem of turnover were considered. A total of 50 questionnaires were distributed and 46 of the administered questionnaire was responded to and returned. The data obtained were analysed with statistical tools such as standard deviation, mean and variance. Also pie charts, bar chart, column chart and line chart were used in presenting results. The four-point Likert scale was used to rank factors in order of their importance based on the relative Important Index (R.I.I) of the factors. The result shows that poor payment and benefits, poor treatment of workers and absence of advancement and promotion opportunities are the main cause of turnover while tribal differences and religious differences as regard cultural diversity are the main factors responsible for turnover. The study observed that craftsmen turnover has both direct cost and indirect cost effect on the performance of construction companies. Cost of hiring new employees, training of new workers and replacing old workers was shown to be the main direct cost effect on the performance of a contractor while indirect cost such as Project overtime, additional workload on remaining workers and reduction of project performance are the main effect of indirect cost. The study also shows that the problem of craftsmen turnover can be reduced by paying competitive compensation and benefit packages, fair treatment of workers and reward for dedicated workers are some of the best ways of reducing turnover while fairness, equal opportunity and respect for all and conducive workplace and cultural relation balance are ways of reducing turnover resulting from the cultural diversity of workers. The study also identified that motivation of craftsmen by increasing wages and salaries, promoting committed workers and training of craftsmen can be used to reduce the effect of craftsmen turnover. Based on the findings in the work, appropriate recommendations were being made to help tackle the challenges of craftsmen turnover in the construction industry.